2019
DOI: 10.1080/00221325.2019.1621259
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Peer Pressure and Adolescents’ Binge Behaviors: The Role of Basic Needs and Coping

Abstract: Framed from a framework based on the integration of SDT (Ryan & Deci, 2000) and Endler and Parker"s conception of coping strategies (1990), the current study analyzed the relationships between peer pressure and binge behaviors (binge eating and binge drinking) in adolescence. Moreover, the study explored the mediating role of satisfaction/frustration of basic psychological needs and coping strategies in these associations. Participants were 570 high school students (M = 15.75; DS = 1.14) living in Italy. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…Moreover, programs should target enhancing parents' awareness of the importance of the use of monitoring strategies and the avoidance of psychologically controlling parenting in preventing children's problem behaviors. According to Inguglia et al (2020) parents should be equipped with skills to keep an eye on their children's activities and relationships without being invasive. This probably would help them to recognize when their children are at risk to develop problem behaviors and to promptly and properly intervene (Inguglia et al 2020;Symeou and Georgiou 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, programs should target enhancing parents' awareness of the importance of the use of monitoring strategies and the avoidance of psychologically controlling parenting in preventing children's problem behaviors. According to Inguglia et al (2020) parents should be equipped with skills to keep an eye on their children's activities and relationships without being invasive. This probably would help them to recognize when their children are at risk to develop problem behaviors and to promptly and properly intervene (Inguglia et al 2020;Symeou and Georgiou 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical support was found for an association between parental control and coping (Chen et al 2016;Nijhof and Engels 2007). In particular, some studies framed on Self-Determination Theory (SDT; Ryan and Deci 2000) argue that parental psychological control is associated with children's coping strategies (Chen et al 2016;Inguglia et al 2020;Nijhof and Engels 2007;Wolfradt et al 2003). For instance, Chen et al (2016) found that need frustration related to controlling parenting may elicit responses that vary from avoidance to emotional responses, including the expression of emotions, self-blame, emotion inhibition and passive acquiescence, in order to escape from the control of parents to reduce the stress related to the control they exert.…”
Section: Parental Control and Adolescents' Problem Behavior: The Rolementioning
confidence: 99%
“…Research has underlined that the satisfaction of these needs is important for managing the social environment and interpersonal relationships, and that meeting these needs enables positive adjustment outcomes, such as higher self‐esteem and life satisfaction (Costa, Soenens, Gugliandolo, Cuzzocrea, & Larcan, 2015; Inguglia, Costa, Ingoglia, & Liga, 2019; Reis, Sheldon, Gable, Roscoe, & Ryan, 2000). Cross‐sectional, longitudinal, and experimental research has extensively shown that basic needs fulfilment (BNF – competence, relatedness, and autonomy) is generally associated with several indicators of subjective well‐being, including positive affect, vitality, school engagement, and life satisfaction (Leversen, Danielsen, Birkeland, & Samdal, 2012; Simões & Alarcão, 2014; Tian, Chen, & Huebner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given their high prevalence and possible detrimental effects, some binge behaviors have received considerable research interest (specifically food and alcohol over-intake), whereas others constitute a topic of increasing research (binge watching or binge porn). However, little is known about the commonalities and differences between binge patterns of behaviors that seem to display overlapping characteristics and similar consequences (for associations between binge eating and binge drinking, see, e.g., Escrivá-Martínez et al, 2020 , Ferriter and Ray, 2011 , Inguglia et al, 2019 , Laghi et al, 2014 , Stickley et al, 2015 ). The identification of common underlying psychological processes between binge behaviors suggests that at-risk individuals may develop several forms of excessive behaviors, crucial information from both a public health and a clinical perspective.…”
Section: Introductionmentioning
confidence: 99%